Biomass Production for Energy in India: Review - Hegazy, Rashad A. (Journal of Technology Innovations in Renewable Energy, 2013)
This paper presents a general view about biomass production in India and its potential energy for use in different fields. India has tremendous potential for energy generation through biomass and its residues. Biomass energy is normally produced from firewood, agricultural residues such as bagasse, crop stalks, animal dung and wastes generated from agro-based industries. With the estimated and predicted values, the generating power from the surplus biomass in India was significant and it will continue to be more effective in future. Residue use as a fuel in India is estimated to be 216 Mt as projected value in 2010, recently, around 605 MW of electricity is being produced from biomass firing and 720 MW from cogeneration activities for residue. About 185 Mt (40%) of the dung collected is used as fuel in cook stoves. The potential for biogas production annually is 8750 million m3 from 251 Mt of dung. The amount of fuel-wood consumption during year 2004 was 205 million tonnes used as fuel for traditional cook stoves with low efficiency, 16 Mt used in industrial sector producing 10 PJ, and it was estimated that the production of fuel wood and charcoal increased to the rate of 1.98 per cent per annum. The total quantity of solid wastes generated in larger towns and cities has been estimated at 40 Mt in 2001, and in 2005 the average MSW generation in overall India was approximately 100,000 Mt/day. For the wastewater in India, in 2010, the energy estimated to be around 3929.8 TJ as energy value of CH4.